Design of Android-Based Food Ordering Information System at RM. Solideo Kuliner - Kevin Jeremi Pesik; Chriestie Ellyane Juliet Clara Montolalu; Wisard Widsli Kalengkongan; Dodisutarma Lapihu; Christian Alderi Jeffta Soewoeh; Yohanes Andreas Robert Langi; Mahardika Inra Takaendengan (Universitas Teknokrat Indonesia, 2025)
The culinary industry in Indonesia has experienced significant growth, yet many restaurants still rely on manual ordering systems. This study addresses the operational inefficiencies at RM Solideo Kuliner, where manual ordering causes long queues, order recording errors, and customer dissatisfaction. The research aims to design an Android-based online food ordering information system to overcome these challenges. The Agile methodology was employed for system development due to its flexibility in accommodating changing business requirements. Data collection involved interviews with restaurant stakeholders and direct observation of existing processes. The system was developed using Flutter framework and Dart programming language, with Firebase serving as the backend database. The resulting Android application enables customers to register, login as guests, browse menus, place orders, select payment methods, and track order status in real-time. Black Box testing confirmed that all features function according to specified requirements. Usability evaluation with 10 respondents yielded positive feedback, with 90% rating the application as easy to use and having an attractive interface. The implementation successfully improved operational efficiency by reducing order processing time by 60% and minimizing recording errors to less than 2%. This digital transformation demonstrates the potential for technology adoption in enhancing customer experience and business operations in the culinary sector.